Organ Function Preservation in Locally Advanced Low Rectal Cancer Through Total Neoadjuvant Therapy: A Case Report and Literature Review - Liu F; Yu L; Zhao Y; Li G; He X (Cancer Management and Research)
Fengyuan Liu,* Li Yu,* Yuanyuan Zhao,* Guoliang Li,* Xinjia He* Department of Radiation Oncology, The Affiliated Hospital of Qingdao University Qingdao, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guoliang Li; Xinjia He, Department of Radiation Oncology, The Affiliated Hospital of Qingdao University Qingdao, Shandong, People’s Republic of China, Email liguoliang@qdu.edu.cn; hexinjia1974@163.comAbstract: Locally advanced rectal cancer (LARC) is a common malignancy that is often managed with neoadjuvant radiotherapy to downstage the tumor and increase the rate of complete response. Recent evidence suggests that total neoadjuvant therapy (TNT) may further improve complete response rates and overall survival compared to conventional treatment methods. This case report describes a 61-year-old male patient with LARC who achieved a clinical complete response following TNT. The treatment regimen followed the CinClare study protocol, which included radiotherapy targeting both the rectum and regional lymph nodes, in combination with chemotherapy consisting of irinotecan and capecitabine. After concurrent chemoradiotherapy, the patient underwent six additional cycles of consolidation chemotherapy, leading to a near-complete clinical response. This case demonstrates the potential effectiveness of a high-intensity, dose-dense regimen involving synchronous radiotherapy followed by a six-cycle consolidation chemotherapy course aimed at optimizing organ preservation. This approach highlights a novel model for enhancing organ preservation in patients with low-grade LARC.Keywords: rectal cancer, total neoadjuvant therapy, organ preservation, case report